Nanoparticles Assisted Remediation for Molasses Based Distillery Waste Contaminated Groundwater - Himanshu Joshi1 and Anil Kumar2, Ashutosh Agarwal1* (Recent Research in Science and Technology, 2010)
Abstract Remediation of contaminated groundwater of any molasses based distillery using nanomaterials may prove to be one of the effective treatment methods. For this purpose magnetite (Fe3O4) nanoparticles were synthesized by the reduction of anhydrous ferric chloride (FeCl3) in natural environment. These nanoparticles were characterized using field emission scanning electron microscopy (FESEM) and X-ray diffraction (XRD) techniques. Due to their infinitesimally small size, the particles were employed for the remediation of contaminated groundwater sample of a distillery. Remarkable decline in the values of color, TOC and TDS were observed in four days upon treatment of 100 mL sample with 0.22 g of freshly synthesized magnetite nanoparticles. Keywords: Groundwater, Distillery, Magnetite, Nanoparticles, Remediation